ANALISIS LAPORAN KEUANGAN UNTUK MEMPREDIKSI KEBANGKRUTAN PADA PT. EXPRESS TRANSINDO UTAMA TBK. - M. Kausar Maulana (Program Studi Magister Manajemen Fakultas Ekonomi Universitas Krisnadwipayana, 2022)
This study aims to predict bankruptcy at PT. Express Transindo Utama, Tbk. from 2014 to 2018 using the Altman Z-score Modified analysis model. PT. Express Transindo Utama, Tbk. engaged in the transportation sector.This type of research is a case study. This study uses secondary data from financial statements. Data collection techniques using purposive sampling. Data were analyzed using qualitative descriptive analysis techniques. The results showed that the company from 2014 to 2016 experienced an indication that it could not be determined whether the company was healthy or bankrupt (gray area). But in 2017 until 2018 the company entered the distress zone.